Examining Accounting And Accountability Issues In Religious Context: Insights From Literature - Hasan Basri; Siti Nabiha Abdul Khalid (Aceh International Journal of Social Science, 2012)
Abstract - Religious organizations play an important role in delivering social services in society and tend to control a sizeable proportion of human, financial and other resources of society (Berger, 2003). However, various financial scandals and lawsuits involving them have raised questions regarding the governance and accountability of these organizations (Siino, 2004; Hamilton, 2006). As such, the insights from the literature on the issues of accounting and accountability in the religious-based organizations, especially the Islamic religious organisations are discussed. In so doing, the nature of religious-based organizations, and the practices of philanthropic institutions in an Islamic context are examined. In addition, the scale of accountability in and insights from previous researches on accounting and accountability practices of religious-based organizations are presented in this paper.